Long-Term Analysis of Recurrence Beyond Milan Criteria Following Ablation of Solitary Early-Stage Hepatocellular Carcinoma ≤3 cm in Potentially Transplantable Patients: A Over 10-Year Survival Study - Chen S; Qi H; Tan H; Cao F; Xie L; Huang T; Wu Y; Wen C; Wang Y; Shen L; Fan W (Journal of Hepatocellular Carcinoma)
Shuanggang Chen,1,2,* Han Qi,1,2,* Hongtong Tan,1,2,* Fei Cao,1,2 Lin Xie,1,2 Tao Huang,1,2 Ying Wu,3 Chunyong Wen,1,2 Yujia Wang,1,2 Lujun Shen,1,2 Weijun Fan1,2 1Department of Minimally Invasive Interventional Therapy, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 2State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for cancer, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 3Department of Interventional Therapy, Shenzhen second People’s Hospital, The First Affiliated Hospital of Shenzhen University, Shenzhen, 518035, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weijun Fan, Email fanwj@sysucc.org.cn; Lujun Shen, Email shenlj@sysucc.org.cnBackground: Salvage liver transplantation is promising for hepatocellular carcinoma(HCC) recurrence post-ablation but is significantly affected by recurrence beyond Milan Criteria (RBM).Materials and Methods: A retrospective cohort study of potentially transplantable HCC patients undergoing ablation between 2007 and 2017 assessed median time to recurrence beyond Milan Criteria(TRBM) via Kaplan-Meier curves and predictive capacity of recurrence and RBM for overall survival(OS) via Receiver Operating Characteristic Curves, and identified independent risk factors for TRBM and RBM via Cox and binary logistic regression models.Results: We enrolled 191 potentially transplantable patients with early-stage HBV-related HCC ≤ 3 cm who underwent ablation. During a median follow-up of 7.64 years, HCC recurrence occurred in 126 patients(65.9%), with RBM 86 patients(45.0%). The median TRBM was 10.54 years. Cumulative survival rates without RBM at 3, 5, 8, 10, and 13 years were 77.3%, 65.9%, 56.5%, 51.0%, and 37.6%, respectively. Multivariable analysis identified older age, C-reactive protein(CRP)≥ 1.81 mg/L, and platelet(PLT)≤ 80× 109/L as independent risk factors for TRBM. Also, cirrhosis, CRP≥ 1.81 mg/L and PLT≤ 80× 109/L were identified as independent risk factors of the occurrence of RBM. Elevated Platelet-CRP Score(PCS), integrating CRP and PLT, correlated significantly with an increased incidence of RBM and a more aggressive phenotype, characterized by vascular invasion or metastatic dissemination (P< 0.05). Notably, RBM was a superior predictive indicator for OS compared to recurrence (P< 0.05).Conclusion: When using ablation as a bridge to liver transplantation for solitary HBV-related early HCC (≤ 3 cm), it is crucial first to identify key preoperative features, including high CRP, low PLT, cirrhosis, and older age. Keywords: hepatocellular carcinoma, hepatitis B virus, ablation techniques, transplantable liver transplantation, recurrence beyond the Milan criteria